المناسبة في سورتي الكهف ومريم - بن موسى, جهاد (University of Eloued جامعة الوادي, 2018)
"ملخص البحث: علم المناسبة من العلوم المهمة التي تعين على فهم القرآن الكريم, حيث يبحث عن سر ترابط الآية بالآية والسورة بالسورة. ويتولى هذا البحث دراسة نظرية لعلم المناسبات, وتطبيق هذا العلم على سورتين من القرآن الكريم هما (الكهف ومريم). حيث تطرقت فيه إلى مفهوم علم المناسبة في اللغة والاصطلاح, وأنواعها, وأهميتها وآراء بعض العلماء فيها, مع أهم المؤلفات في هذا العلم. ثم انتقلت إلى الجانب التطبيقي للدراسة, حيث قمت بتفسير الآيات تفسيرا إجماليا لكلا السورتين وإظهار أوجه المناسبة بين اسم السورة وموضوعاتها, وبين افتتاح السورة وخاتمتها وأخيرا بين مقاطع السورة, مع تقديم بعض العظات والعبر لكل مقطع, وختمت بحثي بأهم النتائج والتوصيات التي توصلت إليها. ومن أبرز ما توصلت إليه: أني لاحظت التكامل التام بين السورتين في معالجة القضية المحورية؛ وهي قضية التوحيد ودرء كل ما حيك حولها من طعون وشبهات خاصة في مسألة البعث والنشور ومسألة الحساب الآخروي. " " Abatract: Knowledge of the occasian of the important sciences that have to understand the holy Quran, where is it looking at the secret of in terdependence verse verse and surah surah. This research is a theoretical study of the science of events, And the application of this science an the two surahs from the Quran which they are (kahfe and Meriem), where i touched on the concept of science of the occasian in the language and terminology, types, importance and opinions of same seientests..with the most important works in this science, then I moved to the practical said and training for the study, i have interpreted the verses as a total interpretatian of the tow surahs and to show the apporopriate aspects between the name of surah and its topics, and between the opening of the surah and its final, and finally between the sectans of the surah, with some sermons and lessons for each section, my research ended with the most important findings and recommendations. And the most prominent of its finding: I noticed full integration between the two surahs in the treatment of the as all issue, this is the issue of Tawheed and the extent to which it is delated whith regard to appeals and suspicions, especially in the matter of Baath, Al-nashur, and the matter of the Hereafter accunt. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: القرآن الكريم، علم المناسبة، الكهف ومريم; "The Holy Quran،Flag the occasion،kahfe and Meriem. "